Nurses’ Participation, Perceived Benefits And Barriers In Health Policy Making In Pakistan - Hussain, Nazir; Mukhtar, Madiha; Masih, Sarfraz (Journal of Neonatal Surgery, 2025)
Background: Nurses globally have close contact with patients and are knowledgeable about their most intuitive conditions. Including them in the policy-making process will enhance the healthcare system and help in sustainable health development. This study aims to determine the factors affecting nurses’ participation in health policy making. It also determine the perceived benefits, Perceived Barriers and its demographic association for nurses’ participation in health policy making, in Pakistan Methodology: A cross sectional analytical study was conducted among registered nurses at various hospitals from Punjab, Sindh, Khyber Pukhtoonkhwa, Balochistan and Islamabad. A probability simple random sample of n=341 participants was recruited. The data collection tools consisted of, nurses’ participation questionnaire, barriers questionnaire and perceived benefits. A written consent was implied to every participant along with the close ended questionnaire. Introduction to every participant was done. After data collection it was entered and analyzed in SPSS version- 21. Results: The study revealed that while nurses in Pakistan recognize the importance of participating in health policy-making, their actual involvement remains limited (71.0%) exhibit low participation. Key perceived benefits included participation builds self-confidence (86.8%), contributes to public health promotion (86.2%), impact on people health (85.3%) and high opportunity to communicate (83.3%). However, significant barriers such as lack of political knowledge (87.4%), an unclear path to gaining necessary information (80.1%), and uncertainty about the efficacy of political activity (85.9%), no any meaningful change (78.9%) and lack of external support (78.9%) and financial resources (61.3%) as significant obstacles. Moreover, age, experience and designation were found to have significant association with the nurses' role in healthcare decision-making. Conclusion: The study highlights that despite recognizing the benefits of health policy participation, most nurses exhibit low involvement due to barriers like limited political knowledge and lack of external support